(untitled) (Materiali di Estetica. Terza serie, 2016)
Being interested in Caravaggio for a long time now, I have wondered if his pictures that involve so much the spectator could be compared to a modern and contemporary communication. In the end I thought the answer would be positive. Moreover, Longhi has already spoken about Caravaggio’s cinematography movie effects. But his own charm, in filming of brutal or sneak action, depends on the singularity of his art work - we as semiotic use to call a text “original”, although it is the countless photographic copy and portrayal. This callback to the origin by a pilgrim is what distinguish the great painting from the great cinema. As Guido Neri well realized, Caravaggio’s painting is the first modern expression of a existentialist sensitivity, unique and so universal.